Effect of communicating personalized rheumatoid arthritis risk on concern for developing RA: A randomized controlled trial - Marshall, Allison A. (Patient Educ Couns, 2018)
OBJECTIVE: To investigate the effect of providing comprehensive personalized risk information on concern for chronic disease development. METHODS: Unaffected first-degree relatives (FDRs) of rheumatoid arthritis (RA) patients (n = 238) were randomly allocated to: 1) disclosure of RA risk personalized to demographics, genetics, biomarkers, and behaviors using a web-based tool (PRE-RA arm, n = 78); 2) PRE-RA with interpretation by a health educator (PRE-RA Plus arm, n = 80); and 3) standard RA education (Comparison arm, n = 80). Concern for developing RA was assessed at baseline and immediately, 6 weeks, 6 months, and 12 months post-intervention. RESULTS: FDRs randomized to PRE-RA arms were less concerned about developing RA than the Comparison arm at all post-intervention assessments (p < 0.05). Among those concerned about RA risk at baseline, the PRE-RA (OR = 4.7, 95%CI 1.5–14.4) and PRE-RA Plus (OR = 5.2, 95%CI 1.6–17.3) arms were more likely to have reassurance 6 months post-intervention than the Comparison arm. CONCLUSION: A comprehensive tool provided reassurance to those at risk for developing a chronic disease, with or without interpretation from a health educator, compared to standard education. PRACTICE IMPLICATIONS: Individuals may be more likely to be reassured using a personalized chronic disease risk disclosure tool than a standard non-personalized approach.